CÁLCULO DE PROPRIEDADES GEOMÉTRICAS USANDO MODELAGEM ISOGEOMÉTRICA (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work presents the implementation of a numerical code for calculating geometric properties of tridimensional objects applying isogeometric analysis and the radial integration method. Initially, it is unfold a brief history indicating the importance of isogeometric design and, following that, the non uniform rational B-Splines (NURBS), the basic structure of isogeometric analysis, are explained. After that, the steps for constructing the algorithm using the radial integration method are described. The radial integration method is used in order to transform volume integrals into surface integrals. The softwares developed in MATLAB were verified with problems which analytic solutions were known. The numeric results are in good agreement with the analytic ones.